Quantifying mangrove export of dissolved organic carbon on large scales and at fine resolution: a review of current technologies and the path forward - Chance W. Sullivan; Neil David Hartstein; Moritz Müller (Discover Oceans)
Abstract Mangroves are carbon dense forests that are threatened by human driven factors. Their ability to sequester carbon can play a key role in meeting climate targets like the Paris Climate Agreement and the United Nations Sustainable Development Goals. In addition to sequestration, mangroves are significant sources of carbon to the ocean sink, which has implications for global carbon budgets. Mangrove carbon export is estimated to be equivalent to about 4% of yearly anthropogenic CO2 emissions. Currently, most estimates of global mangrove dissolved organic carbon (DOC) export are scaled from local analyses. However, mangrove ecosystems are dynamic and local analyses alone are not sufficient for accurate quantification of DOC export. Studies of mangrove DOC export need to expand spatial and temporal scales and refine temporal resolution. Technologies like advanced in-situ sampling, laboratory methods, remote sensing, modelling and machine learning can help to achieve this, but they are underutilised in mangrove DOC export research. In this review we explore the current state, existing and emerging technologies, and future needs for the study of mangrove DOC export.